The Role of Geogebra Software in Stimulating Students' Mathematical Problem Solving Ability - Muhammad Tandhimul Haq; Wati Susilawati; Iyon Maryono; T. Tutut Widiastuti, A (UIN Sunan Gunung Djati Bandung, 2022)
The reasoning ability of students in terms of solving mathematical problems, especially those related to the side of everyday life, is still very low. So that when face-to-face learning is suddenly replaced with online learning, it makes education actors, especially teachers as educators, difficult. Which causes the decline in students' reasoning abilities to solve problem solving problems due to changing learning activities due to the pandemic. This literature study research aims to show an increase in students' mathematical problem solving ability using Geogebra Software as a help application that can be a solution for teacher confusion and to improve problem solving abilities. The method that will be used in the research is literature study. The stages used are taking and collecting various sources that can support from books, websites, journals, theses and others, whose validity can be justified and then processed into a theoretical and accurate conclusion. Results Based on the analysis of the data obtained, the results show that the use of software with the help of the Geogebra application is considered effective and can be a solution to improve abilities in terms of solving mathematical problems